1999
DOI: 10.1542/peds.104.5.e56
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Human Immunodefiency Virus Type 1 Infection in Children: A Five-Year Prospective Study in Rwanda

Abstract: In Africa, HIV-1-infected children develop disease manifestations early in life. Specific clinical findings are predictive of HIV-1 disease, AIDS stage, and death. Bimodal expression of HIV-1 pediatric disease is encountered in Africa, as in industrialized countries, but prognosis is poorer. human immunodeficiency virus infection, children, vertical transmission, natural history, Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
149
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(159 citation statements)
references
References 35 publications
9
149
1
Order By: Relevance
“…Spira et al also stated that cough was not related to HIV. 20 In the present study, 7.4% seropositive children had pneumonia. Pol et al observed 12.68% seropositive children with pneumonia, which is comparable with our study.…”
Section: Discussionsupporting
confidence: 46%
“…Spira et al also stated that cough was not related to HIV. 20 In the present study, 7.4% seropositive children had pneumonia. Pol et al observed 12.68% seropositive children with pneumonia, which is comparable with our study.…”
Section: Discussionsupporting
confidence: 46%
“…In addition, programmes to prevent mother-to-child HIV transmission should use all the opportunities to link infants born to HIV-infected mothers to early treatment of HIV infection to reduce HIV related complications. 3 It is important to note that 67 (66%) admissions were not on ARV therapy at the time of admission. Hospital admissions provide the opportunity for CD4 count and treatment initiation for those patients with the appropriate indications.…”
Section: Discussionmentioning
confidence: 99%
“…2 Challenges to optimal care and treatment in subSaharan Africa include limited resources, staff, and laboratory support. 3 The human professional capacity for delivering HIV/ AIDS care is constrained across much of sub-Saharan Africa, where per capita numbers of physicians and nurses are only 1% to 2% of those of the United States. 4 Unlike adults, children often experience a rapid progression of HIV disease soon after infection because of their immature immune system and persistently high level of plasma virus.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, approximately 35−45% of HIV-1-infected children are estimated to die within the first 24 months of life. 8,9 While public perception assumes that children in this area are prone to malnutrition, no data have been available to support this, or to make comparisons with other populations. As part of a large, randomized, controlled intervention study of insecticide (permethrin)-treated bed nets (ITNs), we monitored all-cause morbidity and standard parameters of malnutrition in a series of cross-sectional surveys involving a random selection of pre-school children.…”
Section: Introductionmentioning
confidence: 99%